Characterization of higher education spatial injustices: Cases of selected Sub-Saharan universities - Khumalo, Shuti Steph (UIN Raden Mas Said Surakarta, 2024)
The primary focus of this study was to explore the experiences of academics in relation to the challenges they face regarding office space. This paper was underpinned by the qualitative exploratory research design within the interpretivist philosophy. This paper explores the varied expressions of participants (three lecturers, two senior lecturers, three associate professors, four full professors, and three managers) through semi-structured interviews on how they characterize spatial challenges in their selected universities. In its examination, I undergirded the thesis of this paper on the social justice theory and on the concept of space as espoused by Lefebre (2004). In addition, extant literature on the epistemology of academic space and academic performance was intensively evaluated. The result of this study provides a glimpse of the socially just challenges academics face regarding office space. This study is of significance because there is scarcity of research on the comparison of office space provision in relation to selected universities in the Sub-Saharan region. In addressing this scholarly gap, the paper provides insights in the epistemology of space, social justice, and academic performance and how space can disrupt the academic agenda.